Proposta de protocolo para colagem ortodôntica com cimento de ionômero de vidro restaurador - Ferri, Patricia Albani (2019)
Composite resin is the most used material for bracket bonding in orthodontic treatment, although it carries the risk of enamel damage and white spots formation. Resin modified glass ionomer cement (RMGIC) has been employed as an alternative for orthodontic bonding, for it allows fluoride release and has lower bond strength than composite resin, thus reducing the risk of enamel damage. However, the only RMGIC specifically indicated for bracket bonding is the Fuji Ortho LC® (GC America Corporation, Tokyo, Japan), which is not always available in all countries due to import issues. The aim here was to evaluate and put forward the use of restorative glass ionomer cements as bonding materials in orthodontics. One hundred and twenty bovine teeth were randomly distributed into six groups (n = 20): FO (teeth moistened with water and brackets bonded with RMGIC Fuji Ortho LC®, as recommended by the manufacturer); RAG ( teeth moistened with water and brackets bonded with Riva LC® RMGIC); RAD (teeth moistened with Prime Bond 2.1® adhesive without photoactivation and brackets bonded with RMGIC Riva LC®); GLAG (teeth moistened with water and brackets bonded with RMGIC Gold Label 2 LC®); GLAD (teeth moistened with Prime Bond 2.1® adhesive without photoactivation and brackets bonded with RMGIC Gold Label 2 LC®); and XT (teeth moistened with Light Cure Adhesive Primer photoactivated for 20 seconds and brackets bonded with Transbond XT® composite resin, as recommended by the manufacturer). All teeth were previously conditioned with 37% phosphoric acid for 20 seconds and photoactivated for 40 seconds after bonding. After 24 hours, the teeth were submitted to the shear bond strength test and photographed with 16-fold magnification to evaluate adhesive remnants, bond fracture surfaces and enamel lesions. One sample from each group was analyzed by scanning electron microscopy and dispersive energy spectroscopy (SEM/EDS), in order to evaluate the material/enamel interface and to conduct a chemical analysis of the materials. Except for the GLAD group, the mean bond strengths of the RMGICs were between 9 and 12 MPa, within the range required to resist chewing and orthodontic movement, with no significant differences between restorative and orthodontic RMGICs (p> 0.05). The moistening with adhesive accounted for the increased bond strength observed in the GLAD group (p 0.05). Enamel fractures occurred in some teeth with bond strength above 13 MPa. After debonding, both restorative and orthodontic RMGICs had less material remaining in the enamel and the bonding failure occurred closer to the enamel/material interface when compared to the composite resin. To use a restorative RMGIC as orthodontic bonding material, the teeth must be pre-conditioned and moistened with water for better protection of the enamel. Moistening the enamel with adhesive instead of water prior to bonding may be indicated where greater bond strength is required.